Integrated Communication Model to Develop Tourism in Coastal Areas of Southeast Sulawesi - Harnina Ridwan; Sarpin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to provide an overview of tourism improvement through communication. The development of tourism in coastal areas requires integrated communication. Improving the image of the destination can be enhanced through effective integrated communication. Local governments can use integrated communication as a driving tool in tourism development. They were using a qualitative approach to describe and describe the core of the problem. Research informants are the government, private sector and the community as stakeholders. Observation, interview and documentation are collection techniques used by authors. The procedure in this study is to simplify the collected data, systematically present the oral data of the interview and recording results into written data, and process, interpret and analyse more comprehensively. Tourism communication is an activity of the government, society and tourism business owners to exchange information about the substance of tourism consisting of tourism marketing activities, delivery of destination image information, messages about accessibility and information on the availability of human resources and Institutional. The outline of the tourism communication model shows the importance of communication elements that frame the overall process of tourism communication channels. The persuasive communication process of mass communication, interpersonal communication and group communication on tourism marketing activities in coastal areas is an integral part of tourism communication